THE PROBLEM OF CHILDREN DURING THE WAR YEARS: REFLECTION IN HISTORICAL MEMORY AND DOCUMENTS - Pirimkulova, Saodat (UZBEKISTAN — 2030: PROSPECTS FOR INNOVATION, SCIENCE AND EDUCATION, 2025)
This article reflects the involvement of the population, especially children, in the evacuation process, in addition to enterprises and institutions evacuated to the rear areas during the Second World War, and the literature and archival documents related to them play an important role. The problem of children during the Second World War was the most global social tragedy, which was reflected in historical memory and archival documents. The article presents research works by Uzbek historians on the role and contribution of Uzbeks to the victory in the Second World War. It evaluates works on military topics written during the Soviet era, as well as research during the period of independence. Currently, we observe a growing interest in the history of the Second World War among young researchers. We should also note the relevance of this issue in terms of falsifying the results of the war against fascism. The fate of children evacuated during the war years is an important source for covering that period, not only in literature and archival documents, but also in state decisions. It is precisely on this topic that the published literature, articles, and especially archival documents are highlighted.